(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
Long Term Evolution mobile communication technology channel resource allocation methods and standards, as well as Round Robin Scheduler, Max C/I Ratio, Best CQI scheduling, Proportional Fair Scheduling algorithm, each has its own function and determines the speed. In terms of the balanced distribution of the bandwidth of the communication channel, the Round Robin and Proportional Fair methods have the best performance and it is found that it is one of the effective methods to ensure the required speed. In Long-Term Evolution technology, transmission can be achieved by solving the distribution problem. As a result of the analysis, we found out the shortcomings of certain methods, as well as promising requirements for solving the problem of allocation of planning blocks between user stations. Using test environments, we modeled the Long-TermEvolution channel resources at two different frequencies in the frequency range below 6 GHz and above 2 GHz in Matlab environment and were able to analyze to see the signal-to-noise ratio level.